Salivary Creatinine is Complementary to Serum Creatinine in Patients with Chronic Kidney Disease (Bangladesh Renal Journal, 2026)
Background: Chronic kidney disease (CKD) diagnosis and staging requires glomerular filtration rate (GFR), which can be estimated by serum creatinine using various equations. Frequent monitoring of serum creatinine and other blood-based renal function tests necessitates repeated venipuncture, which causes anxiety and discomfort to the patient and also contributes to anemia. So, a non-invasive alternative to serum creatinine for screening, diagnosis and monitoring of CKD will be of much value.Objective: This study is planned to assess diagnostic utility of salivary creatinine as complementary to serum creatinine in patients with CKD.Methods: This cross sectional study was conducted in Dhaka Medical College Hospital. A total of 226 participants, comprising 153 cases (group 1) of CKD and 73 healthy controls (group 2) were included in the study by purposive sampling technique. Unstimulated whole saliva and venous blood were collected following standard procedure. After centrifugation, saliva supernatant and serum was analyzed for creatinine concentration by auto-analyzer using Jaffe’s method.Results: Both serum and salivary creatinine levels were significantly higher in CKD patients than that of controls. Among CKD patients, both serum and salivary creatinine levels were incremental across the stages G1-G5. The correlation between serum and salivary creatinine was very weak in controls (r=0.065, p=0.593), but strong in CKD patients (r=0.606, p